Academic self-efficacy and brakers: transactional analysis in students of a private university in Lima - Espíritu Salinas, Natividad (2024)
The research was carried out in the post-Covid 19 phase of the epidemic, after more than two years of virtual higher education. The relationship between academic self-efficacy and emotional and intellectual brakers according to the Transactional Analysis was studied on an intentional sample of 107 students from a private university in Lima, of different professional careers and sexes. The instruments were applied after the informed consent was obtained according to the Helsinki declaration. The Scale of the Expectation of Perceived Academic Self-efficacy EAPESA of Palenzuela was applied and the Questionnaire of Negative Parental Behaviors of Kertész and Tapia of CONANTAL was also used. When interaction indexes between academic self-efficacy and the related to brakes in the emotional and intellectual areas were calculated, non-significant correlations were found. A significant relationship was found between emotional and intellectual brakes in Transactional Analysis.